Using Pabami Media to Improve Early Reading of Cerebral Palsy Students in the 1st Class of the Elementary School for Children with Special Needs - Neny Yuniarti; Yohanes Subasno (Journal of ICSAR, 2022)
The ability to read is the most basic competency to master competencies in other subjects. Learning to read which was carried out at Elementary School for Children with Special Needs (SDLB) YPAC Malang City found that one out of three  students of Cerebral Palsy in 1st class had problems with early reading. One of the causes of not optimal students' reading ability is because teachers tend to only use printed books. Appropriate and interesting media is needed so that students can have reading skills as expected. The purpose of this study is to describe the use of pabami media to improve early reading skills in students of Cerebral Palsy in the 1st class at SDLB YPAC Malang. This research is a classroom action research designed in 2 cycles, each cycle consists of 3 meetings. The learning media used is pabami which is equipped with cards of letter, syllable, and word. Data were collected by observation and test techniques. Pabami media is declared effective if the posttest results in the second cycle are higher than the posttest scores in the first cycle, with learning mastery indicators reaching a value of 75 or more. The results of the study concluded that pabami media was effective for improving early reading skills of students with cerebral palsy.